(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Hidayat S. 2017. The use by local communities of plants from Sesaot Protected Forest, West Nusa Tenggara, Indonesia. Biodiversitas 18: 238-247. Sesaot Protected Forest is a forest area located very close to human settlements in Sesaot Village, Narmada Sub-district, West Lombok District, West Nusa Tenggara, Indonesia. The level of dependence of rural communities on the forest resources is very high. This study aimed to determine the range of utilization of plants made by people living around the forests, and to evaluate conservation needs for these plants. Utilization of the various plants by Sesaot society was observed in an ethnobotanical study employing a combination of open interview techniques and field observation over a two week period. The results of the study showed that there were 61 species of forest plants utilized by the Sesaot people. Among the 61 species, there were species that had a single function or others that had multiple functions. There were 20 species utilized as food and beverage; 19 used as medicines and herbs; and 15 species as building materials. Other species were utilized in a variety of ways: as fuel wood, as material for craft and/or furniture, for animal traps, as food wrappings and as ornamental plants. The part of the plant most widely used was wood (30.8%), either as a building material, as craft material, for firewood, or in medical treatments. The utilization of wood products poses significant risks for the survival of certain tree species, because the timber is generally obtained by illegal logging. It was noted that certain prized timber producing species tend to be targeted by illegal loggers; such as garu (Dysoxylum parasiticum), bajur (Pterospermum javanicum), rajumas (Duabanga moluccana) and some species of Myrtaceae. This study showed that Sesaot Protected Forest has an important role in sustaining the daily life of the surrounding community. However, without strong conservation efforts in the management of Sesaot Protected Forest, it is feared that unsustainable utilization practices will lead to the loss of some important plant species from this region. Keywords: Conservation, plants, protected forest, Sesaot, utilizationÂ